Assessing the impact of oscillating dietary crude protein on the stability of the rumen microbiome in dairy cattle - F. L. Viquez-Umana; M. G. Erickson; J. D. Young; G. I. Zanton; M. A. Wattiaux; G. Suen; H. C. Mantovani (Frontiers in Microbiology)
IntroductionUnderstanding how the rumen microbiota responds to varying protein levels and feeding patterns is critical for optimizing dairy cattle nutrition. This study investigated the influence of dietary crude protein (CP) levels (13.8% or 15.5% CP of ration dry matter) and CP feeding patterns (constant over time (static) or oscillating by 1.8 percentage units above and below the mean every 48 h) on the composition, diversity, and function of the rumen microbiome.MethodsUsing a replicated Latin Square design, eight rumen-cannulated Holstein cows were assigned each of the four dietary treatments (structured as a 2 × 2 factorial) in four consecutive 28-day periods (with 24 days of adaptation and 4 days of sampling). Rumen samples were collected 4 h post-feeding, and amplicon libraries of the V4 region of the 16S rRNA gene were sequenced and analyzed to assess changes in microbiome composition. Additionally, volatile fatty acids (VFAs) were measured to evaluate rumen microbial function.ResultsResults indicated that dietary CP level did not alter microbial diversity (p = 0.30), but oscillating diets increased rumen microbial diversity (Shannon index, p = 0.04). The rumen microbiome richness was also affected by CP feeding pattern (p = 0.05), but not dietary CP level (p = 0.27). Furthermore, differential abundance analysis using ANCOM-BC identified CAG- 352 (p = 0.0001) and an unclassified member of the family Acholeplasmataceae (p = 0.0002) as taxa significantly impacted by protein level and feeding pattern, even though their relative abundance was low (below 0.02%). The functional profile of the rumen bacterial communities was not affected by CP level or feeding pattern, and VFA profiles also remained consistent across treatments, with no observable changes in concentration.DiscussionThese findings support the hypothesis that the rumen microbiome remains stable despite variations in the ruminal supply of dietary CP, suggesting that compensatory mechanisms may be involved. Although oscillating dietary CP concentration might alter the rumen microbiome, further research into rumen metabolic processes and host-microbiome interactions is needed to evaluate if the changes observed in our study are biologically relevant for developing new opportunities to enhance protein nutrition in dairy cattle.